Peningkatan Keterampilan Komunikasi Siswa Kelas VII SMP Negeri 1 Tengah tani Melalui Penerapan Model Cooperative Learning - Aprilia, Dena; Rinto, Rinto; Hidayat, Rahmat (LPPM Politeknik Saint Paul Sorong, 2025)
This research aims to enhance students' communication skills in science education by implementing the STAD-type Cooperative Learning model. The subjects of this study were seventh-grade students at a junior high school, with the learning topics